2018
DOI: 10.1089/ars.2017.7239
|View full text |Cite
|
Sign up to set email alerts
|

The Broad-Spectrum Antimicrobial Potential of [Mn(CO)4(S2CNMe(CH2CO2H))], a Water-Soluble CO-Releasing Molecule (CORM-401): Intracellular Accumulation, Transcriptomic and Statistical Analyses, and Membrane Polarization

Abstract: Aims: Carbon monoxide (CO)-releasing molecules (CORMs) are candidates for animal and antimicrobial therapeutics. We aimed to probe the antimicrobial potential of a novel manganese CORM.Results: [Mn(CO)4S2CNMe(CH2CO2H)], CORM-401, inhibits growth of Escherichia coli and several antibiotic-resistant clinical pathogens. CORM-401 releases CO that binds oxidases in vivo, but is an ineffective respiratory inhibitor. Extensive CORM accumulation (assayed as intracellular manganese) accompanies antimicrobial activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Furthermore, complex 19 exhibited a cytostatic effect in the dark and cytotoxic effect if exposed to light against S. aureus. Mann et al introduced molecule 20 and studied the broad-spectrum antimicrobial potential of the molecules [70,71]…”
Section: Manganese Photoactivatable Co-releasing Molecules (Photocorms)mentioning
confidence: 99%
“…Furthermore, complex 19 exhibited a cytostatic effect in the dark and cytotoxic effect if exposed to light against S. aureus. Mann et al introduced molecule 20 and studied the broad-spectrum antimicrobial potential of the molecules [70,71]…”
Section: Manganese Photoactivatable Co-releasing Molecules (Photocorms)mentioning
confidence: 99%
“…Importantly, CORMs were shown to be more potent bactericides than CO gas due to the accumulation of CORMs inside bacterial cells . Mechanisms underlying the antimicrobial effect of CORMs presumably involve the inhibition of bacterial respiratory chain, the enhancement of reactive oxygen species (ROS) generation, the increase of membrane polarization, and the interference of gene expression, etc. Overall, these results revealed that CO administration may be a useful intervention in microbial infections.…”
Section: The Application Of Co In Disease Therapymentioning
confidence: 99%
“…The side effects of CORMs are unfortunately not restricted to ruthenium-based compounds. Manganese-containing CORM-401 stimulates respiration, depolarizes the cytoplasmic membrane in a manner similar to uncouplers, and elicits the loss of intracellular potassium in E. coli cells [ 100 ]. These properties could explain the increase of the oxygen consumption rate (OCR) in intact mitochondria [ 70 ] in the manner independent from the activation of mitoBK Ca .…”
Section: Carbon Monoxidementioning
confidence: 99%